UNUSUAL ERUPTION OF THE MAIN PUGACHEVO GAS-WATER-LITHOCLASTIC VOLCANO OF SAKHALIN IN WINTER 2005 - Mel'nikov O.A.; Levin B.V.; Ershov V.V. (My University, 2006)
Sakhalin is the only region in the Russian Far East where recent active gas–water–lithoclastic (hereafter, mud) volcanism is widely developed and has long been known. Among four regions of mud volcanism developed on the island, the Pugachevo group of the Great (Main or Central) and two minor (secondary or accessory) volcanoes is characterized by the greatest number of violent eruptive centers, diverse and specific patterns, and very high activity.